ANALISIS PENGARUH KUALITAS PELAYANAN, LOKASI, HARGA SERVICE TERHADAP KEPUASAN PELANGGAN DI BENGKEL MOTOR COMS - Claudia, Vallen Gennysia; Panjaitan, Fery; Zamhari (Jurnal Ilmiah Niaga Bisnis Elektronik, 2023)
This research was entitled: “Analisis Pengaruh Kualitas Pelayanan, Lokasi, Harga service Terhadap Kepuasan Pelanggan di Bengkel Motor Coms”. The purpose of this study was to determine the effect of direct marketing on purchasing decisions either simultaneously or partially. This research was conducted from January 2023 to June 2023. The method used in this study is descriptive with a quantitative approach with the aim of finding the relationship between the independent variables (Service Quality, Location, Service Price.) and the dependent variable (Customer Statisfaction) using a statistical formula. While the statistical formula used to test the hypothesis of Multiple Linear Analysis. The sample in this study amounted to 94 people. The results of the study prove that: (1) Service quality has an effect on Customer Statisfaction,tcount value is 2.704 greater than the ttable 1.98667.(2) Location does not affect Customer Statisfaction value of tcount -1523 is smaller than ttable 1.98667. (3) Service price has an effect on Customer Statisfaction,tcount value is 3.470 greater than the ttable 1.98667.